2018
DOI: 10.1002/jaal.904
|View full text |Cite
|
Sign up to set email alerts
|

“I'd Still Prefer to Read the Hard Copy”: Adolescents’ Print and Digital Reading Habits

Abstract: Does print still matter in this digital age? What is the role of technology in reading? Do adolescents who enjoy reading view the reading of print and digital material differently from those who do not enjoy reading? Drawing on survey data from 6,005 students and focus group data with 96 students across six secondary schools, the authors conducted a mixed‐methods study to examine adolescents’ print and digital reading habits in Singapore. Findings show that adolescents prefer print but move toward more online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 23 publications
2
49
2
1
Order By: Relevance
“…For teenagers, peer influence and interactions are important in cultivating positive reading attitudes (Merga, 2014). The social behaviours around reading are also mirrored online where students engage in online reading communities, especially through following authors and the reviews of other readers on fanfiction website (Loh & Sun, 2019). When the reading platform is online, students also rely on their social relationships with friends as part of their strategy for finding stories they like to read online.…”
Section: Affordances Of Digital Readingmentioning
confidence: 99%
See 1 more Smart Citation
“…For teenagers, peer influence and interactions are important in cultivating positive reading attitudes (Merga, 2014). The social behaviours around reading are also mirrored online where students engage in online reading communities, especially through following authors and the reviews of other readers on fanfiction website (Loh & Sun, 2019). When the reading platform is online, students also rely on their social relationships with friends as part of their strategy for finding stories they like to read online.…”
Section: Affordances Of Digital Readingmentioning
confidence: 99%
“…While students may prefer digital platforms for leisure and personal reading (Singer & Alexander, 2017), especially when these readings did not require any form or note-taking, they still find print reading favourable for academic materials (Foasberg, 2014;Loh & Sun, 2019). However, as digital texts are increasingly used to complement print texts in the school curriculum (Walsh, 2010), students will need to develop the skills to read and work with digital texts effectively and be guided by the purpose rather than be passively influenced by the medium.…”
Section: Affordances Of Digital Readingmentioning
confidence: 99%
“…But it not the only reason. There is also an understanding of the meaning of "successful reading" and for a successful career, a successful life -an understanding of reading as a strategy of life is formed [25,26]. This is especially true today, in the conditions of the formation of the digital age.…”
Section: в мире книгmentioning
confidence: 99%
“…Another study was done by Loh & Sun (2018) entitled, "I'd Still Prefer to Read the Hard Copy": Adolescents' Print and Digital Reading Habits" They found out that found that the students in Singapore still prefer print books, even when given the choice of digital copies of books. However, these students do not completely eschew e-books and other online reading resources, but will use them depending on the context.…”
Section: Related Studymentioning
confidence: 99%